Distribution of stable isotopes of Mo and W from a river to the ocean: signatures of anthropogenic pollution - Matsuoka, Kohei; Tatsuyama, Tomomichi; Takano, Shotaro; Sohrin, Yoshiki (Frontiers in Marine Science, 2023)
Molybdenum and tungsten are redox-sensitive elements, and their stable isotope ratios have attracted attention as paleoceanographic proxies. However, our knowledge of the distribution of stable Mo and W isotopes in the modern hydrosphere remains limited. In this study, we provided the concentrations and isotope ratios of dissolved Mo and W in the oceans (the North Pacific and Indian Oceans), marginal seas (East China and the Sea of Japan), and a river-estuary system in Japan (from the Uji-Yodo rivers to Osaka Bay). In the North Pacific and Indian Oceans, the W concentration was 48.2 ± 6.2 pmol/kg (ave ± 2sd, n = 109), δ186/184W was 0.52 ± 0.06 ‰, the Mo concentration was 105.1 ± 8.0 nmol/kg, and δ98/95Mo was 2.40 ± 0.06 ‰. The results indicate that W has the constant concentration and isotopic composition in the modern ocean as well as Mo. In the East China Sea and the Sea of Japan, the W concentration and δ186/184W in the upper water (< 1000 m depth) were different from those in the ocean (W = 56 ± 18 pmol/kg, δ186/184W = 0.45 ± 0.06 ‰, n = 24). However, the concentrations in deeper water were congruent with those in the oceans (W = 49.9 ± 7.6 pmol/kg, δ186/184W = 0.50 ± 0.02 ‰, n = 7). The Mo concentration was 105.4 ± 3.1 nmol/kg and δ98/95Mo was 2.36 ± 0.03 ‰ (n = 31) throughout the water column, congruent with those in the ocean. In the Uji River-Yodo River-Osaka Bay system, the W concentration reached 1074 pmol/kg and δ186/184W reached 0.20 ‰. We propose that the enrichment of W with a low δ186/184W in the river-estuary system and marginal seas is caused by anthropogenic pollution. Anthropogenic Mo pollution was not detected in marginal seas. However, the Mo concentration and δ98/95Mo showed high anomalies above the mixing line of river water and seawater in the lower Yodo River and Osaka Bay, implying possible anthropogenic pollution of Mo in the metropolitan area.